2021
DOI: 10.1111/jpn.13668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mulberry Leaf powder on reproductive performance, serum indexes and milk amino acid composition in lactating sows

Abstract: Experiment was conducted to study the effects of Mulberry Leaf (ML) powder on reproductive performance, serum and milk amino acid composition in sows. Fifty sows (D 85 at gestation) with parity 3 or 4 were randomly divided into 5 groups: C, M100, M200, M300 and M400, receiving 0, 100, 200, 300 and 400 g ML powder per sow per day. Blood and milk of sows at Days 1 and 21 of lactation were collected. Results showed that average daily feed intake (ADFI) during lactation was higher in groups supplemented ML compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In traditional Chinese medicine, mulberry leaves are commonly used to regulate reproductive system hormone levels and their anti-inflammatory properties [ 20 , 21 ]. 1-DNJ (1-Deoxynojirimycin) is a unique natural active component found in mulberry sericulture products, primarily present in the branches, leaves, and roots of the mulberry tree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional Chinese medicine, mulberry leaves are commonly used to regulate reproductive system hormone levels and their anti-inflammatory properties [ 20 , 21 ]. 1-DNJ (1-Deoxynojirimycin) is a unique natural active component found in mulberry sericulture products, primarily present in the branches, leaves, and roots of the mulberry tree.…”
Section: Discussionmentioning
confidence: 99%
“…Mulberry leaves have been used for a long time to treat male and female sexual reproductive function in Chinese traditional medicine. At present, mulberry leaves and their extracts are widely used to improve the reproductive capacity of female animals [ 20 , 21 ]. Mulberry leaf extracts have been shown to reduce the consumption of testosterone in diabetic male rats [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no new eligible studies were identified by reviewing the reference lists of relevant articles. Finally, a total of 18 studies were included in the meta-analysis [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Several studies have investigated the effects of a mulberry leaf diet on various poultry and livestock, however, their results have been inconsistent [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Moreover, no systematic review has yet summarized the effects of mulberry leaves on the growth, production performance, gut microbiota, and immunological parameters of poultry and livestock.…”
Section: Introductionmentioning
confidence: 99%